2018
DOI: 10.1063/1.5050120
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical survey on plants used as traditional salad food (ulam) in Kampung Taun Gusi, Kota Belud Sabah, Malaysia

Abstract: Abstract.A preliminary ethnobotanical survey of traditional salad food or ulam was conducted within Sama-Bajau community in Kampung Taun Gusi, Kota Belud Sabah, Malaysia on May 2017.Three key informants were selected using snowball sampling technique, and data about traditional salad food (ulam) were collected by semi-structured interview and field observation. A total of 28 species of plants from 26 genera and 20 families were recorded have been consumed as ulam. The study also reveals apart from being consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The leaves are consumed as vegetable by the local people of Jombang, East Java, and Kapuas Hulu in West Borneo and by the Saibatin sub-tribe in Lampung of Indonesia (Haryanti et al 2015;Sholichah and Alfidhdhoh 2020;personal observation). The same has also been reported from Northeast Thailand, and Malaysia (Awang-Kanak et al 2002;Suksri et al 2005;Ong et al 2012). Leaves are also processed into softdrinks in Cambodia, Thailand, and Vietnam.…”
Section: Local Food Usessupporting
confidence: 74%
See 1 more Smart Citation
“…The leaves are consumed as vegetable by the local people of Jombang, East Java, and Kapuas Hulu in West Borneo and by the Saibatin sub-tribe in Lampung of Indonesia (Haryanti et al 2015;Sholichah and Alfidhdhoh 2020;personal observation). The same has also been reported from Northeast Thailand, and Malaysia (Awang-Kanak et al 2002;Suksri et al 2005;Ong et al 2012). Leaves are also processed into softdrinks in Cambodia, Thailand, and Vietnam.…”
Section: Local Food Usessupporting
confidence: 74%
“…The Temiar women folk claim that the leaves of Centella asiatica are also good to promote overall health during postpartum (Zaki et al 2019). The leaves are eaten fresh, as it is believed to cure memory loss, and also act as antiaging medicine, by the local people of Kampung Taun, Kota Belud Sabah (Awang- Kanak et al 2002). It is also reported that the local people of Masjid Ijok in Perak State use the infusion of the whole plant to delay aging (Ramli et al 2015).…”
Section: Local Medicinal Usesmentioning
confidence: 99%
“…Dusun of Kampung Pinolobu also eat fruit of Passiflora foetida to reduce high blood pressure. However, the Sama Bajau of Kampung Taun Gusi were previously reported to only consume the fruit (Awang-Kanak et al, 2018a).…”
Section: Resultsmentioning
confidence: 99%
“…In Kota Belud, Sabah (Malaysia), young leaves of C. caesia are often consumed raw as salad (ulam) by the Sama-Bajau people. Te leaves are freshly eaten or given as a drink to treat cough [12].…”
Section: Traditional Usesmentioning
confidence: 99%